The use of anthropomorphic agent in movie: case study of Cast Away (2000) / Azahar Harun and Mohameed Razeef Abd Razak - Harun, Azahar; Abd Razak, Mohameed Razeef (Faculty of Art and Design, 2019)
This paper presents a case study of a Hollywood blockbuster movie called Cast Away (2000). The analysis is based on two anthropomorphism theories called Familiar Thesis and Comfort Thesis. Categorised under adventure drama, Cast Away (2000) depicts a story of a Federal Express executive named Chuck Noland who survives a plane crash and is stranded on an uninhabited island in the Pacific for four years. Cut off from the modern world, Chuck adapts to the harsh environment of the tropical island by salvaging FedEx packages washed up on the beach. One of the packages contains a Wilson volleyball which later in the plot becomes Chuck’s companion. This study employs a scene-by-scene analysis approach to understand how anthropomorphism theories are exploited and presented in the plot. From this, several important scenes that promote the meaning of life and social relationships have been discovered. In this regard, the study concludes that the Wilson volleyball is not just an advertising gimmick but an anthropomorphic agent that helps provide companionship, care, comfort and motivation which are essential for human survival.